Modelling kinetics of thermal degradation of colour in peach puree - Ávila, I.M.L.B. (1999)
Optimisation of thermal processes relies on adequate degradation kinetic models for food safety and quality. In order to use peach puree as a model food to further validate calculated optimal conditions, isothermal experiments, using peach puree, were performed between 110°C and 135°C. Colour was quantified using the L, a, b system. Two combinations of these parameters, La/b and Total Colour Difference (TCD), were used to evaluate the total colour change. A one-step non-linear regression was performed on all data using the Arrhenius model. The changes in the L and b values followed a first-order reaction with activation energies of 107 ± 7 and 109 ± 8 kJ/mol, respectively. The fractional conversion model was applied to a, La/b and TCD resulting in activation energies of 106 ± 13, 106 ± 10 and 119 ± 9 kJ/mol, respectively.